How to cheat at configuring ISA server 2004 - Shinder, Thomas W.; Shinder, Debra Littlejohn (Rockland, Mass. : Syngress, 2006)
How to Cheat at Configuring ISA (Internet Security and Acceleration) Server 2004 meets the needs of system administrators for a concise, step-by-step guide to getting one of Microsoft's most complex server products up and running. While books twice its size may be perfect for network designers and security specialists, this is written for the person in the trenches actually running the network day to day. How to Cheat at Configuring ISA Server 2004 is written for the vast majority of Windows System Administrators with too much to do and too little time in which to do it. Unlike books twice its size, this is a concise, to-the-point guide. * Administrators daily jobs - too many mission critical tasks in too little time. A quick reference to ISA Server * Written by Dr. Tom Shinder, the undisputed authority on Installing, Configuring, Managing and Troubleshooting ISA Server * Includes independent advice on when the "Microsoft Way" works, and when another approach might be more appropriate to your situation.
ISA 2004 network concepts and preparing the networks infrastructure -- ISA 2004 client types and automating client provisioning -- Instaling and configuring the ISA firewall software -- Creating and using ISA 2004 firewall access policy -- Publishing network services with ISA 2004 firewalls -- Creating remote access and site-to-site VPNs with ISA firewalls -- ISA 2004 stateful inspection and application layer filtering -- Accelerating web performance with ISA 2004 caching capabilities -- Using ISA Server 2004's monitoring, logging, and reporting tools.
Includes index.
Keywords: Microsoft ISA server; Firewalls (Computer security); Computer networks -- Security measures; Internet -- Security measures -- Software; Microsoft ISA server; Electronic books; Software